Relationship between the Deterioration of Multi Story Buildings Facades and the Driving Rain - Melo Júnior,Carlos Mariano (Escuela de Construcción Civil, Pontificia Universidad Católica de Chile, 2014)
In order to evaluate the behavior of facades in relation to driving rain, as well as the influence of the architectural elements in front of the deterioration, were calculated in this work the monthly directional driving rain index (dDRI-m) and the amounts of driving rain wall index (I0) to the city of Goiania, Brazil. Was performed a study of case over staining on facades through visual inspection and photographic record of buildings rendered with mortar and paint finish, with more than 12 story and construction aged 10 or under, located in the same city. Samples were collected on facades regions with stains for microbiological analyzes. As a result, it was found that facades of the same building are subject to different levels of moisture and deterioration, fact established by the correlation between the staining observed in the studies of case and the dDRI-m and I0. The stains, often described as dirt, showed the presence of microorganisms: filamentous fungi, phototrophics and actinomycetes.